Notícias on-line: estratégias enunciativas de apelo ao sensível - Boff, Josiane (2017)
This search is about the study of enunciative strategies presented in journalistic news. It has the main goal to identify and to analyze enunciative strategies related to the projection of passionate effects in online journalistic news. The corpus is composed by an online news titled: “I got petrified”, says the photographer who took the photo of the Syrian boy and it was published on the online G1 website on the 3rd September of 2015. The analyze is supported on enunciative studies by the Discursive Semiotic perspective. The choice of this approach is justified by the fact that this theory turns to the study of different enunciative mechanisms (verbal and nonverbal), trying to explain how the senses are constructed from their inter-relation in the text. Therefore, the theoretical- analytical basis is based on the studies of Greimas (2013, 2014), Fiorin (2003, 2006, 2014, 2016), Barros (2005, 2012a, 2012b), Gomes (2005, 2007, 2008, 2009) e Teixeira (2004). About the methodological procedures, this corresponds to a bibliographic search, of an applied nature and qualitative approach. As results, we verified that enunciative strategies used in the narrator‘s verbal enunciation project effects of objectivity and neutrality. However, when the delegation of voice to the interlocutors occurs, these can manifest their opinions without restrictions. Then, in the news that we analyzed, there were evidences of effects of passionality in the instance of the interlocutor, when this is manifested in direct speech (verbal or nonverbal). In the verbal enunciations of these people, subjectivity signs and expressions of appeal to the sensitive appear. Also in the photos and videos, considered in this study a species of nonverbal direct speech, passional appeal mechanisms are manifested. In them, the strategies are more evident, because of the photo impact and the audiovisual resources in the productions of reality effects and in the projection of elements of the nature ―unspeakable‖.